Analysis of Intermodal Freight Transport Efficiency: Study of the Java-Sumatra Route - Faris Nofandi; Alwi Sina Khaqiqi; Rizki Adi Pratama (Institut Teknologi Sepuluh Nopember, 2023)
As an archipelagic country, Indonesia has abundant natural resources and the potential to develop various industries. In this case, the Ministry of Industry still relies on Java as a location to encourage industrial activities in Indonesia. One of the largest industrial areas in Indonesia is located in the western area of Java Island, namely in the Pulogadung, Karawang, and Bekasi areas. Geographically, Indonesia, an archipelagic country, has good inter-island connectivity. The maritime transportation sector is a strategic component forming the national transportation system. Apart from that, the competitiveness of Indonesian commodities, goods, and services is developed due to national logistics prices, which are partly determined by transportation costs. The many commodities produced on Java Island have resulted in a high demand for goods from Java Island. The cost of shipping goods plays a significant role in the buyer's price. In this research, several options were analyzed for sending goods from Java to Sumatera, namely by using a truck and then crossing by ship from Merak Port to Bakauheni Port or sending by ship to Panjang Port, from Tanjung Priok Port or Ciwandan Port. This research was conducted to select a mode of transportation with a minimum unit cost to support delivery activities. Then, this research was carried out using an optimization method to make the shipping costs incurred more optimal. The results of this research will provide an analysis of the efficiency of intermodal transportation in transporting goods on the Java-Sumatera route.